A new novel six-degree of freedom two-link manipulator using active magnetic bearing: Design, kinematics, and control. (10th December 2018) - Selmy, Mohamed; Fanni, Mohamed; Mohamed, Abdelfatah M; Miyashita, Tomoyuki
Due to the absence of mechanical contact, active magnetic bearing can be electrically controlled in an accuracy of a micrometer. This makes it a good choice to be used for robot manipulation in the micrometer scale, especially in environments that need to be very clean, for example, surgery or clean rooms. Moreover, it can be used in the applications that need high precision micromotion such as semiconductor wafers manipulation. Despite all these benefits, there are few studies that have investigated the application of active magnetic bearing in the robotics field in spotless environments for micromotion applications. This article proposes a new novel six-degree of freedom two-link manipulator using two contactless joints with active magnetic bearing. The key design aspects of the proposed manipulator are presented. The proposed manipulator is designed using finite element method. Each joint roll angle is controlled using a PID-based feedback linearization controller, while a state feedback controller with integral term is used for controlling the active magnetic bearing five-degree of freedom. The stability analysis of the system, under the proposed controller, is carried out. The robustness of the controllers is tested against end effector payload variations. The results demonstrate that the proposed two-link manipulator is feasible and valid for the applications in spotless environments that need high precision accuracy micromotion control. These significant findings have indicated the feasibility of implementing this proposed manipulator in practice and open the door for developing other types of robots with complete contactless joints using active magnetic bearing.